Dose of vaccine applied against COVID-19 and recovery of the patient treated in the ICU-COVID. EsSalud-Lambayeque contingency Hospitals. December 2021-February 2022. - Pecsén Monteza, José Enrique (2023)
Introduction: Vaccination against COVID-19 has been shown to reduce the risk of morbidity and mortality in the severe form of COVID and hospitalization in susceptible patients. Objective: To determine if there is a relationship between the number of doses of vaccine applied against COVID-19 and the recovery of the patient treated in the ICU of EsSalud-Lambayeque Contingency Hospitals between December 2021 and February 2022. Materials and methods: A descriptive study was proposed. , transversal, correlational and retrospective; in a sample of 94 patients hospitalized in the ICU of the Luis Heysen Inchaustegui and Almanzor Aguinaga Asenjo Hospitals, randomly selected. Using a data collection form validated by experts, information was obtained from the medical records of the institutional computer network, maintaining confidentiality and ethical standards. For the analysis, percentages, frequencies and Chi Square were used for the relationship of categorical variables. Results: 60.64% were found to be male, average age 64.38 +/-13.65 years, 53.19% had one comorbidity, 21.27% had two or more, highlighting Arterial Hypertension and Diabetes Mellitus. . 35.11% did not have vaccines, 34.04% second dose, 23.40% third dose and 7.45% first dose. In the ICU discharge condition, 43.62% recovered. The recovery of the patient with the first dose was 57.14% (p<0.008), second dose in 65.63% (p<0.00002) and third dose 50% (p<0.003) Conclusions: If there is a significant relationship between the number of doses of the COVID-19 vaccine and the recovery of the patient in the ICU, a higher prevalence of males, older adults and comorbidities such as arterial hypertension and diabetes mellitus.